1985
DOI: 10.1139/p85-139
|View full text |Cite
|
Sign up to set email alerts
|

Solar-grade silicon substrates by a powder-to-ribbon process

Abstract: A new technique for producing silicon ribbons for solar-cell substrates is described. The process begins with inexpensive, 98% pure silicon that is crushed and acid leached to raise the purity to 99.9%. This powder is spread on a graphite plate and electron-beam annealed to form a flat, self-supporting "preribbon." After removal of the graphite and unmelted powder, the preribbon is given a second electron-beam scan that recrystallizes the silicon into a smooth polycrystalline ribbon. This zone melting further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 1 publication
(3 reference statements)
0
8
0
Order By: Relevance
“…Dietl reported that the best purification results were obtained by using hydrochloric acid and hydrofluoric acid mixtures and finely ground MG-Si (20 μm or less), with a particle size much below the grain size of MG-Si [11]. Norman et al obtained 99.9% Si by leaching in three successive steps with aqua regia, hydrofluoric acid, and hydrochloric acid [12]. Wang and Yin et al upgraded crushed MG-Si from 98 % to 99.96% through leaching by various acids [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Dietl reported that the best purification results were obtained by using hydrochloric acid and hydrofluoric acid mixtures and finely ground MG-Si (20 μm or less), with a particle size much below the grain size of MG-Si [11]. Norman et al obtained 99.9% Si by leaching in three successive steps with aqua regia, hydrofluoric acid, and hydrochloric acid [12]. Wang and Yin et al upgraded crushed MG-Si from 98 % to 99.96% through leaching by various acids [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Dietl (1983) obtained the optimal purification result by utilizing the acid mixture of hydrochloric acid and hydrofluoric acid. Afterwards, Norman et al (1985) demonstrated that upgraded silicon with 99.9% purity can be achieved by leaching in three successive steps with aqua regia, hydrofluoric acid and hydrochloric acid, with an average particle size of 100 mesh.…”
Section: Introductionmentioning
confidence: 99%
“…Dietl (1983) got Hydrometallurgy 121-124 (2012) the best purification result by using a mixture of HF and HCl and finely ground MGSi (b20 μm). Norman et al (1985) refined MGSi to 99.9% pure Si by successive leaching with aqua regia, HF and HCl. Voos (1961) has developed a process to produce silicon suitable for microwave diodes by the treatment of MGSi with aqua regia, H 2 SO 4 and HF.…”
Section: Introductionmentioning
confidence: 99%